The affective economy of feminist leadership in Finnish universities: class-based knowledge for navigating neoliberalism and neuroliberalism. Issue 1 (2nd January 2021) - Morley, Louise; Lund, Rebecca W. B.
ABSTRACT: Women leaders are frequently treated as one class – a homogenised group with essentialised skills and competencies in binary relationship to male leaders. We explore how feminist ways of knowing gender and leadership, and circulations of affects, shape women's diverse leadership practices and identities within the neoliberal, and neuroliberal academy in Finland – a Nordic country with a sophisticated gender equality policy architecture. We debate the (re)production of social and material inequalities through epistemic injustice by exploring what possibilities are emerging from the assemblages and relational potential of policy interventions, global speaking back to patriarchal power, the revisioning of gender, and the inclusion of women in higher education leadership. Theoretically, the study intersects feminist affect notions, neoliberalism, neuroliberalism, and epistemic inclusion/injustice. We conducted 10 interviews with middle-class ed women university leaders in five universities. They described how, in the absence of possibilities to facilitate major structural changes, they applied their feminist knowledge and invested affective labour in the mediation of neoliberal and neuroliberal cultures. The politics of representation – counting more women into neoliberal universities, as one class, is not, we conclude, a counter-normative force. We need to consider how to apply feminist knowledge for leading post-gender universities and imagining alternative futurities.